IS IT NECESSARY TO REBUILD GROUP WORK IN LEARNING? - Ummi Rasyidah (JEE (Journal of English Education), 2016)
The use of cooperative learning in classroom activities is not a new thing. The current study investigates the strength and weaknesses of dynamic and static group formation. 33 students of English Study Program participated in the study. The study mainly focused on students’ perception regarding the group formation during classroom activities. By applying open- ended interview, students’ perception were recorded about possible benefit and disadvantages related to group formation. Overall, this study provides evidence both dynamic and static group formation can facilitate learning.